Forms of aesthetic experience in visual arts as theorization around a referential process of research-creation (Islas, 2024)
Introduction: After essential methodological clarifications about research-creation as a typology of research in the arts, a theoretical construction process is developed for a situated understanding of the notion of aesthetic experience.Methods: The process takes place within the context of accompanying a collective and synchronous research-creation process in visual arts. Through observation and critical analysis, specific manifestations of the visual aesthetic experience are identified, described, and categorized.Results: A refined concept of aesthetic experience is provided, and three specific categories are identified and described, as manifested in a set of 40 research-creation exercises in visual arts.Conclusions: Research-creation proceeds through the construction of an aesthetic experience, which, based on traditional and contemporary creative exercises, can be classified as contemplative, empathetic, or immersive. These categories have specific characteristics that encompass a stylistic, technical, and expressive diversity of great richness in visual arts.
Keywords: visual arts; aesthetics; contemplative aesthetic experience; empathetic aesthetic experience; immersive aesthetic experience